Compact broadband circularly polarized slot antenna with artificial magnetic conductor reflector. Issue 12 (2nd November 2022) - Han, Liping; Chai, Kun; Han, Guorui; Chen, Xinwei; Zhang, Wenmei
Abstract: A compact broadband circularly polarized slot antenna for Sub‐6G applications is proposed in this article. It is composed of a broadband slot antenna exited by a Γ‐shaped microstrip feedline and an artificial magnetic conductor (AMC) reflector with a wide in‐phase reflection phase bandwidth. A unidirectional circularly polarized radiation is achieved by using the AMC reflector consisting of 6 × 6 modified Jerusalem cross unit cells. A prototype of the proposed antenna is fabricated. The impedance bandwidth and axial ratio bandwidth of the antenna is 40.78% (3.26–4.93 GHz) and 39.02% (3.3–4.9 GHz), respectively.